Influence of Rhizospheric Bacteria on Plant Secondary Metabolites - Newmei, Kungkamliu (My University, 2024)
The rhizospheric bacterial microbiome influenced by plant roots plays a vital role in plant growth and promotion and protects the plant from pathogens. Through enhancing plant growth and promotion, the rhizospheric bacteria can alter the synthesis of plant secondary metabolites. This study used a GC-MS-based untargeted metabolomic approach for the metabolic profiling of Coriander sativum grown under various treatments with bacteria. The plant roots were inoculated with the isolated bacteria from the soil and two specific plant growth-promoting rhizobacteria (PGPRs), Pseudomonas azotoformans and Bacillus megaterium. Additionally, the effects of rhizospheric bacteria on plant growth parameters were evaluated. The plants treated with the two specific PGPRs showed an enhancement in root length. Cinnamic acid is higher in plants treated with bacteria than in untreated plants. Fewer pathways were observed in untreated plants than in other treatments, showing the influence of rhizospheric bacteria on plant secondary metabolites. These findings suggest the use of beneficial rhizospheric bacteria such as PGPRs and plant secondary metabolites in agricultural and pharmaceutical sections.
Keywords: Coriander; Metabolome; Microbiome; Rhizosphere; Metabolomic